A plastic surgery service response to COVID-19 in one of the largest teaching hospitals in Europe. Issue 6 (June 2020) - Armstrong, A.; Jeevaratnam, J.; Murphy, G.; Pasha, M.; Tough, A.; Conway-Jones, R.; Mifsud, R.W.; Tucker, S.
Summary: COVID-19 is presenting a colossal challenge to frontline NHS staff. This paper highlights how plastic surgery teams can use their diverse skills and resources in times of crisis. Through effective strategy and leadership we present how we are adapting as a department to serve our plastic surgery patients, other hospital teams and the Trust.